Pharmapolymers in the 21st century: Synthetic polymers in drug delivery applications. (December 2018) - Englert, Christoph; Brendel, Johannes C.; Majdanski, Tobias C.; Yildirim, Turgay; Schubert, Stephanie; Gottschaldt, Michael; Windhab, Norbert; Schubert, Ulrich S.
Graphical abstract: Abstract: The administration of drugs, as a main challenge of pharmaceutical and medicinal applications, has certainly benefited from the application of synthetic polymers. However, despite an enormous effort to develop new materials for drug delivery applications, only few of them have entered the market due to the hurdles of regulation, production, cost efficiency and both industrial's and patients' acceptance. In this review, we summarize all these classes of synthetic polymers, which are on the market as well as the latest developments in clinical trials, and describe their application in polymer-drug conjugates, as excipients, in nano-/microscopic and macroscopic drug carriers, as polymeric coatings, or as polymeric drugs. Our intention is to create a link between the underlying chemical structures, the properties of the polymers, and their area of application, where they are often just known by their trade names or abbreviations. In addition selected types of synthetic polymers are highlighted that feature interesting properties and have the potential to make it to the market in future.